Analisi delle associazioni a Nannofossili calcarei di età eocenica inferiore e media del Site U1410 (Newfoundland Ridge, NO Atlantico): un approccio integrato - Lobba, Veronica (2022)
This Master thesis is the biostratigraphic, biocronologic and isotopic study of a sedimentary succession retrivered during the Expedition IODP 342 at Site U1410 (Newfoundland Ridge, North-western Atlantic Ocean). The biostratigraphic study of calcareous nannofossils assemblages allows for the construction of a precise biostratigraphic framework based on the recognition of the first and last appearance of the several taxa. The age model of the study section indicates that the sediments were deposited during the early Eocene (52.6 to 48.0 Ma) spanning an interval of ca. 4.5 Myr. According to the biozonations available, the study extends from Zone NP11 to Zone NP14 (Martini, 1971), from Subzone CP9b to Subzone CP12b (Okada & Bukry, 1980) and from Zone CNE3 to Zone CNE7 (Agnini et al., 2014). Along the study section, calcareous nannofossils assemblages display a major change, which consists of the first appearance of genera Dictyococcites and Reticulofenestra. This change coincides with the Early Eocene Climatic Optimum (ca. 52-50 Myr) represents a major step toward the establishment of the present day calcareous nannofossils assemblages. The integration of oxigen and carbon stable isotope with calcareous nannofossils relative abundance data permits to frame the observed paleontological changes in a high resolved paleoclimatic scenario. The CaCO3 curve evidences for a remarkable litological change, from pelagic carbonate-rich sediments (nannofossils ooze) to hemipelagic clay-rich terrigenous sediments. This change occured at the early to middle Eocene transition (ca. 48 Myr) and likely documents the onset of Atlantic Deep Western Boundary Current that has flowed off the eastern coasts of North America since then. open